Ankle fractures and dislocations: A pictorial review. (July 2013) - Richards, PJ; Charran, AK; Singhal, R; McBride, DJ
Ankle fractures and dislocations are common injuries. The aim of this pictorial review is to illustrate their radiological assessment, the normal anatomy, the radiographic techniques and the classification of fractures and dislocations in and around the ankle. The mechanism of injury will also be described, which not only can help in classifying the injury, but may also aid in deciding their management. This is not a comprehensive surgical review; however, the importance of determining whether fractures are stable or unstable and the various treatment options are discussed .